2003
DOI: 10.1364/ol.28.002491
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength division with three-dimensional couplers fabricated by filamentation of femtosecond laser pulses

Abstract: Refractive-index changes can be induced by filamentation of 800-nm, 1-kHz femtosecond laser pulses in silica glass. Two-dimensional translation of a 40-microm-long filament leads to the formation of a curved waveguide because of bending by the previously induced refractive-index change. The fabrication of 2-mm directional couplers to split the coupled beam into 1:1 at a wavelength of 632.8 nm is demonstrated. The realization of three-dimensional directional couplers and wavelength division in the output from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…Among these unique advantages of fs laser micromachining, one of important applications is 3D refractive index modification (positive or negative index change with isotropic or anisotropic properties) depending on the laser parameters [7,8]. It was capable and suitable for formation of waveguides, gratings, splitters, couplers, and optical amplifiers etc [1,[9][10][11] by using refractive index change inside glasses. However, the physical origin of the fs laser induced refractive index change (RIC) inside glass still has some controversies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these unique advantages of fs laser micromachining, one of important applications is 3D refractive index modification (positive or negative index change with isotropic or anisotropic properties) depending on the laser parameters [7,8]. It was capable and suitable for formation of waveguides, gratings, splitters, couplers, and optical amplifiers etc [1,[9][10][11] by using refractive index change inside glasses. However, the physical origin of the fs laser induced refractive index change (RIC) inside glass still has some controversies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Little et al [13] revealed that the mechanism of RIC induced by fs laser is depended on the irradiation conditions. There have been many investigations which focused on low repetition-rate regime fs laser (generally 1 kHz) induced RIC [1,[9][10][11][12][13]. However, the RIC induced by low repetition rate fs laser is small (generally about 10 −3 or 10 −4 ), optical elements e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafast laser processing has been extensively applied to fabricate 3D photonic devices such as optical couplers and splitters [84], volume Bragg gratings [85], diffractive lenses [86], Mach-Zehnder interferometers (MZIs) [87], and waveguide lasers [88,89]. Such photonic devices rely on the writing of 3D optical waveguides that can be easily inscribed in transparent materials such as glass, crystalline materials, and polymers by inducing permanent refractive index changes in the focal volumes of tightly focused ultrafast laser pulses [90].…”
Section: D Photonic Devicesmentioning
confidence: 99%
“…12(a)). This two-step procedure results in the formation of 3D microfluidic structures inside glass such as photosensitive glass [96,98,99] and fused silica [84,100]. The microchannels fabricated by FLAE inevitably become wider than the laser-exposed regions and are tapered because of an etch selectivity ratio of approximately 50 between the laser-exposed and laser-unexposed regions.…”
Section: D Microfluidics and Optofluidicsmentioning
confidence: 99%
“…In the last decade there has been a growth attention on methods to process materials for the development of devices. Femtosecond laser micromachining has prompted as a potential approach in this direction, enabling the production of several optical devices, from interferometers to waveguide couplers [9][10][11][12][13][14][15][16]. This technique presents several advantages when compared to other approaches, being a direct processing method, single-step and maskless [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%